On the utility function of experiments in fundamental science - Tommaso Dorigo; Michele Doro; Max Aehle; Muhammad Awais; Nicolas R. Gauger; Rafael Izbicki; Jan Kieseler; Ann B. Lee; Luca Masserano; Federico Nardi; Alexander Shen; Luis Recabarren Vergara (Physics Open)
The majority of experiments in fundamental science today are designed to be multi-purpose: their aim is not simply to measure a single physical quantity or process, but rather to enable increased precision in the measurement of a number of different observable quantities of a natural system, to extend the search for new phenomena, or to exclude a larger phase space of candidate theories. Most of the time, a combination of the above goals is pursued; this breadth of scope adds a layer of complexity to the already demanding task of designing the measurement apparatus in an optimal way, by defining suitable geometries and choosing the most advantageous materials and appropriate detection technologies. The precise definition of a global optimality criterion may then require experimentalists to find a consensus on the relative scientific worth of those goals.In this work we discuss the problem of formulating a utility function for multipurpose experiments, as an enabling step to employ artificial intelligence tools to explore the design space and assist humans in finding solutions at the Pareto front. For that purpose, we consider two use cases in particle physics research and one in astro-particle physics; in the latter case we show, using a recently developed optimization software, how the precise definition of a multi-target utility function may enable a significant increase of its value above that offered by human-designed detector layouts.